An integrated approach for predicting the shear capacity of fibre reinforced concrete beams. (1st November 2018) - Barros, Joaquim A.O.; Foster, Stephen J.
Highlights: Integrated design approach for determining the shear capacity of flexurally reinforced SFRC members. The approach considers fibre distribution profile, fibre pull-out resistance and the MCFT. The most complete experimental data base on the shear behaviour of R/SFRC is provided. The proposed approach performs well when compared with the results of the data base. The proposed approach predicts better than the two ones recommended by the CEB-FIP Model Code 2010. Abstract: This paper describes the development of an integrated design approach for determining shear capacity of flexurally reinforced steel fibre reinforced concrete members. The approach considers fibre distribution profile, fibre pull-out resistance and the modified compression field theory integrated using a comprehensive strategy. To assess the performance of the developed model, a database consisting of 122 steel fibre reinforced and prestressed concrete beams failing in shear was assembled from available literature. The model predictions were shown to correlate well with the test data. The performance of the analytical model was also compared to predictions attained by the two approaches recommended by the fib Model Code 2010, one based on an empirical equation and the other on the modified compression field theory approach. The predictive performance of the proposed approach was also assessed by using the Demerit Points Classification ( DPC ), being the prediction as better as lower is the total penalty points provided by the classification. The model developed in this paper demonstrated a superior performance to those of the Model Code, with a higher predictive performance in terms of safety and reliability.